Editorial: Flight Information Region: Safety or Sovereignty Issues - Latipulhayat, Atip (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2018)
Editorial: Flight Information Region: Safety or Sovereignty Issues